Baseline soil-transmitted helminth and schistosome infection in the Geshiyaro project, Ethiopia: A unique transmission interruption project using biometric fingerprinting for longitudinal individual analysis. - Anna E Phillips; Alison K Ower; Kalkidan Mekete; Ewnetu Firdawek Liyew; Rosie Maddren; Birhan Mengistu; Ufaysa Anjulo; Melkie Chernet; Julia C Dunn; Hussein Mohammed; Habtamu Belay; Bokretsion Gidey; et al. (Public Library of Science (PLoS), 2023)
Background The Geshiyaro project aims to assess the feasibility of interrupting transmission of soil-transmitted helminths (STH) and schistosome (SCH) infection in the Wolaita zone of southern Ethiopia through high coverage community-wide mass drug administration (MDA), in combination with improved water, sanitation, and hygiene services and behaviour change communication delivered through the existing health care infrastructure. To accurately measure treatment coverage a population census was conducted enrolling individuals with biometric fingerprinting and barcoded ID cards. This paper details the baseline census and parasitology surveys conducted before the start of any interventions. Methods The census was conducted in five of the 15 Wolaita districts between October 2018 and December 2019, enrolling all consenting participants from every household. Simultaneously, a cross-sectional parasitology survey was conducted in 130 out of 361 randomly selected communities from all 15 districts, with 100 individuals across all age groups (infant to adult) per community providing stool and urine for analysis by duplicate Kato-Katz and a point-of-care circulating cathodic antigen (POC-CCA) to test for Schistosoma mansoni and STH, and microhaematuria and urine filtration for Schistosoma haematobium. Of the 130 communities, 30 were randomly selected for annual, longitudinal parasitological monitoring, with 150 randomly selected individuals from infant to adult providing two days of stool and urine samples for analysis by the same diagnostic tests per community. Results In total 97,919 households participated in the baseline census enrolling 466,071 individuals, with parasitological data obtained from 10,785 people. At baseline, 15.5% were infected with at least one STH species, with Ascaris lumbricoides (9.5%), followed by hookworm (7.2%) and Trichuris trichiura (1.8%). Substantial heterogeneity in STH prevalence was observed between communities ranging from 0% to 61% where most infections were low intensity. Schistosoma mansoni infection was the dominant schistosome infection (0.85% by Kato-Katz and 13.3% by POC-CCA trace negative and 21.5% trace positive), with few Schistosoma haematobium infections identified (2.77% haematuria positive and 0.13% positive by urine filtration). Conclusions While the national control program in Ethiopia has made good progress in reducing prevalence of STH and SCH in Wolaita since it was launched in 2015, there remain areas of persistent infection suggesting the existence of environmental or behavioural risk factors that contribute to ongoing transmission. This project aims to identify the most efficient intervention strategies to reduce community burden and reach interruption of transmission.